The Objectivity of Intellectual Property Rights in Indonesia - Chow, Andrew; Xu, Low Wei; Sukanto, Vanessa Evelyn (Anthology: Inside Intellectual Property Rights, 2023)
Indonesia as a rechtsstaat, all positive laws must be obeyed and enforced to protect the interests of the people and the State. It is the duty of law enforcement officers to enforce the law in a bold and fair manner. The word objectivity we assert is defined as the lack of favoritism toward one side or another. Our group chose this topic because we have seen and read many cases in Indonesia where it is debatable whether verdicts are made fairly and that goes against the principle of legal certainty. We find that objectivity should be at the very center of Intellectual Property Rights (“IPR”). Our group feels that the Law of IPR in Indonesia in both enforcement and substance has failed to achieve justice, and rather has served to create confusion and has greatly harmed the corporate climate of Indonesia. This article will attempt to clarify the exact factors that are behind this issue and explain all the implications of a faulty IPR law, be it social, economic or political.